Pulses in Indo-Gangetic Plains Status and strategies for area expansion and productivity gain - Ali, Masood; Kumar, Narendra (Indian Farming, 2016)
During Green Revolution period, Indo-Gangetic Plains witnessed a sea change in cropping pattern, with rice-wheat covering over 10 million ha As a consequence of this, pulses were marginalzed. Whereas, wheat area increased by 58.6 % during 1970-75 to 2010-14, the pulse area decreased by 52.4% during the same period. The share of pulses in food grain acreage of IGP decreased from16.7% to 7.0 %. This is posing a serious threat to nutritional security and sustainable crop production. Low yield of pulses coupled with high instability in production led to gradual decline in its area which is alarming and needs to be reversed. Three-pronged strategies (a) expanding area under pulses through intercropping, catch cropping and introduction in rice fallows, (b) improving genetic yield potential through widening genetic base and employing transgenic technology and (c) improved crop management practices need to be adopted to address the emerging challenges.